Susceptibility-weighted magnetic resonance imaging for the evaluation of deep infiltrating endometriosis: preliminary results - YOLDEMİR, AHMET TEVFİK (SAGE PUBLICATIONS LTD, 2016)
Background: Knowledge of the precise sites of deep infiltrating endometriosis (DIE) lesions is essential for preoperative workup and treatment. Susceptibility-weighted imaging (SWI) has high sensitivity for blood products and have recently been applied in abdominal imaging. Purpose: To determine the value of SWI in the diagnosis of DIE. Material and Methods: Forty-three clinically suspected DIE patients with sonographically diagnosed ovarian endometriomas who had tenderness or palpable nodule(s) on rectovaginal examination were referred to pelvic magnetic resonance imaging (MRI) including SWI. Two patients were excluded from the study because of low quality of SWI series. Twenty-eight patients who were offered laparoscopic endometriosis surgery (LES) preferred medical treatment over surgical approach. Thirteen out of 41 participants had LES. Lesions were evaluated for their locations, signal intensities on T1-weighted (T1W) and T2-weighted (T2W) images, and presence of signal voids on SWI using 3T MRI and correlated with LES findings. Results: A total of 18 endometriosis foci were laparoscopically removed from 13 patients. DIE lesions removed at laparoscopy were located at the uterosacral ligament (9/18), rectovaginal region (4/18), retrocervical region (2/18), and fallopian tubes (3/18). Eleven out of 18 (61%) DIE foci were detected by their high-signal intensities on T1W images whereas 16 out of 18 (89%) DIE foci were detected by signal voids on SWI. Conclusion: SWI imaging with its high sensitivity to blood products, contributes to the diagnosis of DIE by depicting different phases of hemorrhage not seen by conventional MRI sequences.
Keywords: Endometriosis; susceptibility-weighted imaging (SWI); deep infiltrating endometriosis (DIE); magnetic resonance imaging (MRI); PELVIC ENDOMETRIOSIS; TRANSVAGINAL SONOGRAPHY; CLINICAL EXAMINATION; DIAGNOSIS; WALL; ULTRASOUND; EXPERIENCE; FEATURES; MASSES; MRI